1996
DOI: 10.1093/ajcp/105.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Correlates With Peripheral Blood Morphology and Immunophenotype in Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is recognized as a distinct entity. However, morphologic and immunophenotypic heterogeneity exist. Twenty-six patients with CLL were studied to investigate whether an association exists among peripheral blood karyotype, morphology and immunophenotype. Clonal cytogenetic abnormalities were detected in 14 patients (53%), using conventional karyotyping techniques in addition to fluorescence in situ hybridization (FISH) for chromosome 12. By FAB guidelines, 7 of the 8 patients (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 0 publications
1
54
0
Order By: Relevance
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 83%
See 2 more Smart Citations
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 83%
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71). Furthermore, cases of CLL with trisomy 12 have been shown to be associated with an atypical immunophenotype including increased CD20 expression (66,70) and expression of FMC7 (65,68,70,71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 87%
See 1 more Smart Citation
“…Most of the Correspondence: F Ajchenbaum-Cymbalista; Fax: 33 1 42 34 82 54 Received 7 January 1998; accepted 20 April 1999 studies conducted on atypical B-CLL have been devoted to their immunologic characteristics 2,3 or to cytogenetic abnormalities, [4][5][6][7][8][9][10][11] but clinical presentation and outcome have not been extensively studied, although they are considered as sharing a poorer prognosis than typical CLL. 12 Among the recurrent genetic alterations observed in B-CLD, the translocation t (11;14) has been recently highlighted, since it is the hallmark of MCL.…”
Section: Introductionmentioning
confidence: 99%
“…These studies report a correlation between atypical morphology and trisomy 12, although definitions of atypical vary among investigators. [10][11][12][13] In a recent study correlating karyotype with lymphocyte morphology and immunophenotype in CLL, we noted an association between trisomy 12 and atypical morphology defined as CLL, mixed-cell type. In addition, we were intrigued by an apparent association between structural abnormalities of chromosome 13ql4 and typical CLL morphology, although this observation was based on only three cases within the study population.…”
mentioning
confidence: 99%